A kind of segmented purification method of natural graphite

Through segmented alkali treatment, microwave treatment, acid treatment and microwave treatment, the problems of low purity and reduced conductivity of natural graphite are solved, and the purification of graphite with high purity and excellent conductivity is achieved.

CN119143125BActive Publication Date: 2025-01-21ZIBO QINGDA POWDER MATERIAL ENG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411666420.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-01-21
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

In the prior art, natural graphite has a problem that the purity of the natural graphite is low and the conductivity decreases after purification.

Method used

Adopt segmented alkali treatment, microwave treatment, acid treatment and microwave treatment methods. The specific steps include mixing and grinding natural graphite with sodium hydroxide, microwave treatment, then circulating treatment in hydrofluoric acid, adding metal salt solution and Microwave irradiation was performed under an argon atmosphere.

Benefits of technology

Through this method, the purity and conductive properties of graphite can be significantly improved, ensuring the high purity and excellent conductive properties of graphite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application belongs to the field of graphite purification, and particularly relates to a segmented purification method for natural graphite. The method provided by the present application is to mix and grind natural graphite with sodium hydroxide, rapidly cool down after microwave treatment, and then microwave treat after hydrofluoric acid circulation treatment to obtain a high-purity graphite product. The present application is to solve the problem that the purity of natural graphite in the prior art is low and the conductivity is reduced after purification. The segmented purification method of natural graphite provided by the present application obtains high-purity graphite with excellent conductive properties through segmented alkali treatment, microwave treatment, acid treatment, and microwave treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of graphite purification, and in particular relates to a segmented purification method for natural graphite. Background Art

[0002] Natural graphite is a mineral composed of carbon and is one of the allotropes of carbon. It mainly exists in rocks in nature, in the form of flakes or blocks, and is widely distributed around the world. Natural graphite has unique physical and chemical properties, which makes it occupy an important position in industrial and technological applications. Graphite has good thermal and electrical conductivity, can withstand high and low temperatures, and resist chemical corrosion. The graphite structure has a certain regular rigidity and strength, and can maintain its firmness and strength even at nearly 4000°C. Therefore, it is also widely used in chemical industry, metallurgy, new energy, electronic information, military industry, aerospace and other related fields. It has become one of the indispensable raw materials in the field of high-precision and cutting-edge technology in the 21st century. Natural graphite is increasingly used as anode materials for lithium batteries. Anode materials refer to materials used as cathodes in electrochemical devices. These materials participate in electrochemical reactions during the charging and discharging of batteries and are usually used in lithium-ion batteries, nickel-hydrogen batteries and other types of batteries. The selection of anode materials has an important impact on the performance of batteries, such as capacity, cycle life, energy density and safety.

[0003] Natural graphite usually contains various impurities, such as metal elements, silicates and other minerals. These impurities will affect the performance and application effect of graphite. The beneficiation process of natural graphite can only achieve a graphite purity of 96% at most. The remaining impurities such as silicon, magnesium, calcium, iron, and aluminum mineral impurities need to be removed by chemical reaction. With the continuous development of technology, ordinary high-carbon graphite products can no longer meet the requirements of various industries, and the purity of graphite needs to be further improved. Graphite purification mainly adopts physical or chemical methods. Chemical methods generally include alkaline acid method, hydrofluoric acid method, mixed acid leaching method, chlorination roasting method and high-temperature roasting method.

[0004] Patent CN102583360A discloses a method for purifying graphite with microwaves. Step 1: add graphite to a sodium hydroxide solution, then place it in a microwave reactor, stir it thoroughly, seal it and apply microwave energy, alkali leaching for 20 to 90 minutes, then cool it to room temperature, and separate the graphite from the alkali solution; step 2: add the graphite treated in step 1 to a hydrochloric acid solution, then place it in a microwave reactor, seal it and apply microwave energy, acid leaching for 20 to 90 minutes, then cool it to room temperature, separate the graphite from the acid solution, and wash it with distilled water or deionized water until it is neutral; step 3: dry the graphite treated in step 2 at a temperature of 80 to 250°C for 30 to 180 minutes. This method can obtain high-purity graphite, but acid leaching or alkali leaching and microwave treatment are carried out simultaneously. Due to the strong oxidizing property of graphite during acid leaching, the interlayer spacing of graphite is enlarged, and sp with good conductivity is obtained.2 The hybrid structure transforms into a non-conductive sp 3 The structure, coupled with the auxiliary effect of microwaves, further reduces the conductivity of graphite, and the pressure conditions of 1 to 15 atm need to be maintained during the microwave treatment step, which also increases the difficulty of the process operation. Summary of the invention

[0005] In order to solve the problems in the prior art that natural graphite has low purity and reduced conductivity after purification, the present application provides a segmented purification method for natural graphite. The scheme provided in the present application obtains high-purity graphite with excellent conductive properties through segmented alkali treatment, microwave treatment, acid treatment, and microwave treatment.

[0006] The present application provides a method for segmented purification of natural graphite, comprising the following steps:

[0007] S1. Put natural graphite and sodium hydroxide into a ball mill for mixed grinding;

[0008] S2, subjecting the ground product obtained in S1 to microwave treatment for 10-20 min, and then rapidly cooling it with cold water and drying it;

[0009] S3, placing the product obtained in S2 in a circulation reactor and treating it in hydrofluoric acid, maintaining a constant temperature of 50-70° C. for 2-3 hours in a circulation mode;

[0010] S4, filtering the product obtained in S3 and mixing it with a metal salt solution, heating it to 70-85°C and maintaining it for 5-6 hours, cooling the mixture to room temperature, filtering it and drying it, and irradiating the dried product with microwaves under an argon atmosphere for 5 min-10 min to obtain a purified graphite product.

[0011] Furthermore, the mass ratio of the natural graphite to the sodium hydroxide in step S1 is (2-4):1.

[0012] Furthermore, the grinding time in step S1 is 15-30 minutes.

[0013] Furthermore, in step S3, the weight ratio of the product obtained in S2 to the hydrofluoric acid solution is 1:2-3.

[0014] Furthermore, the concentration of the metal salt solution prepared in step S4 is 0.05-0.08 mol / L, and the mass ratio of the metal salt solution to the product obtained in S3 is 10-15:1.

[0015] Furthermore, the metal salt is one of nickel sulfate, iron nitrate, cobalt nitrate or chromium nitrate.

[0016] Furthermore, the argon flow rate in step S4 is 1-2 L / min.

[0017] Furthermore, the microwave frequency in steps S2 and S4 is 2450 MHz.

[0018] The beneficial effects of this application are:

[0019] The technical solution of the present application mixes natural graphite with sodium hydroxide and grinds it, and through mechanical action, that is, using the high-energy impact and friction generated by the ball mill to destroy the van der Waals force between graphite layers, the graphite particles are refined, and the sodium hydroxide can be inserted between the graphite layers to form an intercalation compound, which is conducive to further changes in the graphite structure during subsequent processing, improves the reactivity of graphite, and facilitates subsequent processing. Microwaves can penetrate deep into the material, generate a thermal effect, and accelerate the decomposition of the sodium hydroxide intercalation compound.

[0020] Hydrofluoric acid is a strong acid that can effectively remove impurities on the graphite surface and has a good removal effect on non-carbon elements in graphite. Constant temperature treatment in a circulating reactor can ensure uniform reaction and improve purification efficiency. The addition of metal salt solution can form metal deposition on the graphite surface. These metal particles will produce local thermal effects under microwave irradiation, which will help further purify the graphite and remove residual impurities. At the same time, microwave treatment under argon atmosphere can prevent metal oxidation and ensure the quality of the final product.

[0021] The prior art combines acid leaching with microwave treatment to obtain high-purity graphite. However, due to the strong oxidizing property of the acid leaching process, the interlayer spacing of the graphite is enlarged, and the sp 2 The hybrid structure transforms into a non-conductive sp 3 The structure, coupled with the auxiliary effect of microwaves, further reduces the conductivity of graphite. The inventors found in their research that carrying out acid leaching and microwave treatment in stages can actually improve the conductivity of graphite, and the high purity of graphite is also guaranteed through the process. DETAILED DESCRIPTION

[0022] The technical scheme of the present invention and its effects are further described below by specific examples. The following examples are only used to illustrate the content of the present invention and are not used to limit the protection scope of the present invention. Simple changes made to the present invention by applying the concept of the present invention are all within the scope of the protection claimed by the present invention.

[0023] The equipment used in the preparation method of the present invention can be the well-known equipment in the art. The raw materials used in the present invention are commercially available unless otherwise specified.

[0024] Example 1

[0025] S1. Put natural graphite and sodium hydroxide with a mass ratio of 2:1 into a corrosion-resistant ball mill for mixed grinding at a speed of 400 r / min and a grinding time of 30 min;

[0026] S2, putting the ground product obtained in S1 into a 1000W, 220V microwave oven, setting the microwave frequency to 2450MHz, and microwave treating for 10 minutes. After the treatment, cool the temperature to room temperature quickly with 5-10°C cold water and dry it;

[0027] S3, placing the product obtained in S2 in a circulation reactor, treating it in 10wt% hydrofluoric acid, with a solid-liquid weight ratio of 1:2, and maintaining the temperature at 50°C in the circulation mode for 2 hours;

[0028] S4. Mix 1g of the product obtained by S3 with 100mL of 0.05mol / L nickel sulfate solution, raise the temperature to 70°C and maintain for 5 hours, then cool the mixture to room temperature, filter and dry in an oven at 60°C for 5 hours, and irradiate the dried product in a 1000W, 220V microwave oven under argon atmosphere with a microwave frequency set to 2450MHz for 5 minutes to obtain a graphite product with a purity of 99.997%.

[0029] Example 2

[0030] S1. Put natural graphite and sodium hydroxide with a mass ratio of 4:1 into a corrosion-resistant ball mill for mixed grinding at a speed of 400 r / min and a grinding time of 15 min;

[0031] S2, put the ground product obtained in S1 into a 1000W, 220V microwave oven, set the microwave frequency to 2450MHz, and microwave for 20min. After the treatment, cool it to room temperature quickly with 5-10℃ cold water and dry it;

[0032] S3, placing the product obtained in S2 in a circulation reactor, treating it in 10wt% hydrofluoric acid, with a solid-liquid weight ratio of 1:3, and maintaining a constant temperature of 70°C in a circulation mode for 3 hours;

[0033] S4. Mix 1g of the product obtained from S3 with 150mL of 0.08mol / L ferric nitrate solution, raise the temperature to 85°C and maintain for 6 hours, then cool the mixture to room temperature, filter and dry in an oven at 60°C for 5 hours, and irradiate the dried product in a 1000W, 220V microwave oven under argon atmosphere with a microwave frequency set to 2450MHz for 10 minutes to obtain a graphite product with a purity of 99.998%.

[0034] Example 3

[0035] S1. Natural graphite and sodium hydroxide with a mass ratio of 3:1 are put into a corrosion-resistant ball mill for mixed grinding at a speed of 400 r / min and a grinding time of 20 min;

[0036] S2, put the ground product obtained in S1 into a 1000W, 220V microwave oven, set the microwave frequency to 2450MHz, and microwave for 15 minutes. After the treatment, cool it to room temperature quickly with 5-10℃ cold water and dry it;

[0037] S3, placing the product obtained in S2 in a circulation reactor, treating it in 10wt% hydrofluoric acid, with a solid-liquid weight ratio of 1:3, and maintaining a constant temperature of 60°C in a circulation mode for 2.5 hours;

[0038] S4. Mix 1g of the product obtained from S3 with 120mL of 0.06mol / L ferric nitrate solution, raise the temperature to 80°C and maintain for 5.5 hours, then cool the mixture to room temperature, filter and dry in an oven at 60°C for 5 hours, and irradiate the dried product in a 1000W, 220V microwave oven under argon atmosphere with a microwave frequency set to 2450MHz for 7 minutes to obtain a graphite product with a purity of 99.997%.

[0039] Comparative Example 1

[0040] S1. Put natural graphite and sodium hydroxide with a mass ratio of 2:1 into a corrosion-resistant ball mill for mixed grinding at a speed of 400 r / min and a grinding time of 30 min;

[0041] S2, putting the ground product obtained in S1 into a 1000W, 220V microwave oven, setting the microwave frequency to 2450MHz, microwave treatment for 10min, leaving it to cool at room temperature and then drying;

[0042] S3, placing the product obtained in S2 in a circulation reactor, treating it in 10wt% hydrofluoric acid, with a solid-liquid weight ratio of 1:2, and maintaining the temperature at 50°C in the circulation mode for 2 hours;

[0043] S4. Mix 1g of the product obtained by S3 with 100mL of 0.05mol / L nickel sulfate solution, raise the temperature to 70°C and maintain for 5 hours, then cool the mixture to room temperature, filter and dry in an oven at 60°C for 5 hours, and irradiate the dried product in a 1000W, 220V microwave oven under argon atmosphere with a microwave frequency set to 2450MHz for 5 minutes to obtain a graphite product with a purity of 99.995%.

[0044] Comparative Example 2

[0045] S1. Add natural graphite into 15% sodium hydroxide solution, the mass ratio of natural graphite to sodium hydroxide is 2:1, and soak for 30 minutes;

[0046] S2, put the product obtained in S1 into a 1000W, 220V microwave oven, set the microwave frequency to 2450MHz, and microwave for 10 minutes. After the treatment, cool it to room temperature quickly with 5-10℃ cold water and dry it;

[0047] S3, placing the product obtained in S2 in a circulation reactor, treating it in 10wt% hydrofluoric acid, with a solid-liquid weight ratio of 1:2, and maintaining the temperature at 50°C in the circulation mode for 2 hours;

[0048] S4. Mix 1g of the product obtained by S3 with 100mL of 0.05mol / L nickel sulfate solution, raise the temperature to 70°C and maintain for 5 hours, then cool the mixture to room temperature, filter and dry in an oven at 60°C for 5 hours, and irradiate the dried product in a 1000W, 220V microwave oven under argon atmosphere with a microwave frequency set to 2450MHz for 5 minutes to obtain a graphite product with a purity of 99.950%.

[0049] Comparative Example 3

[0050] S1. Put natural graphite and sodium hydroxide with a mass ratio of 2:1 into a corrosion-resistant ball mill for mixed grinding at a speed of 400 r / min and a grinding time of 30 min;

[0051] S2, placing the product obtained in S1 in a circulation reactor, treating it in 10wt% hydrofluoric acid, with a solid-liquid weight ratio of 1:2, and maintaining the temperature at 50°C in the circulation mode for 2 hours;

[0052] S3. Mix 1g of the product obtained by S2 with 100mL of 0.05mol / L nickel sulfate solution, raise the temperature to 70°C and maintain for 5 hours, then cool the mixture to room temperature, filter and dry in an oven at 60°C for 5 hours, and irradiate the dried product in a 1000W, 220V microwave oven under argon atmosphere with a microwave frequency set to 2450MHz for 5 minutes to obtain a graphite product with a purity of 98.742%.

[0053] Comparative Example 4

[0054] S1. Put natural graphite and sodium hydroxide with a mass ratio of 2:1 into a corrosion-resistant ball mill for mixed grinding at a speed of 400 r / min and a grinding time of 30 min;

[0055] S2, putting the ground product obtained in S1 into a 1000W, 220V microwave oven, setting the microwave frequency to 2450MHz, and microwave treating for 10 minutes. After the treatment, cool the temperature to room temperature quickly with 5-10°C cold water and dry it;

[0056] S3, 1g of the product obtained by S2 was mixed with 100mL of 0.05mol / L nickel sulfate solution, heated to 70°C and maintained for 5 hours, then the mixture was cooled to room temperature, filtered and dried in an oven at 60°C for 5 hours, and the dried product was irradiated with microwaves at 1000W, 220V in an argon atmosphere for 5 minutes at a microwave frequency of 2450MHz;

[0057] S4. The product obtained in S3 is placed in a circulation reactor and treated in 10 wt% hydrofluoric acid. The temperature is kept at 50°C for 2 hours in the circulation mode. After filtering, it is dried to obtain a graphite product with a purity of 99.852%.

[0058] Comparative Example 5

[0059] S1. Add natural graphite to 15% sodium hydroxide solution, the mass ratio of natural graphite to sodium hydroxide is 2:1, put it into a 1000W, 220V microwave oven, set the microwave frequency to 2450MHz, microwave treatment for 10 minutes, filter it after the end, quickly cool it to room temperature with 5-10℃ cold water and dry it;

[0060] S2. The product obtained in S1 was placed in 10wt% hydrofluoric acid with a solid-liquid weight ratio of 1:2, and microwaved for 5 minutes in a 1000W, 220V microwave oven with a microwave frequency set to 2450MHz to obtain a graphite product with a purity of 98.719%.

[0061] Comparative Example 6

[0062] S1. Put natural graphite and sodium hydroxide with a mass ratio of 2:1 into a corrosion-resistant ball mill for mixed grinding at a speed of 400 r / min and a grinding time of 30 min;

[0063] S2, putting the ground product obtained in S1 into a 1000W, 220V microwave oven, setting the microwave frequency to 2450MHz, and microwave treating for 10 minutes. After the treatment, cool the temperature to room temperature quickly with 5-10°C cold water and dry it;

[0064] S3, placing the product obtained in S2 in a circulation reactor, treating it in 10wt% hydrofluoric acid, with a solid-liquid weight ratio of 1:2, and maintaining the temperature at 50°C in the circulation mode for 2 hours;

[0065] S4. Dry the product obtained in S3 in an oven at 60° C. for 5 hours, put it into a 1000 W, 220 V microwave oven, set the microwave frequency to 2450 MHz, and microwave treat it for 5 minutes to obtain a graphite product with a purity of 98.926%.

[0066] The graphite powders obtained in Examples 1-3 and Comparative Examples 1-6 were pressed into cylindrical samples and the resistivity test was performed using a resistivity tester:

[0067]

Claims

1. A method for purifying natural graphite in stages, characterized in that The following steps are involved: S1. Put natural graphite and sodium hydroxide into a ball mill for mixed grinding; S2, subjecting the ground product obtained in S1 to microwave treatment for 10-20 min, and then rapidly cooling it with cold water and drying it; S3, placing the product obtained in S2 in a circulation reactor and treating it in hydrofluoric acid, maintaining a constant temperature of 50-70° C. for 2-3 hours in a circulation mode; S4, filtering the product obtained in S3 and mixing it with a metal salt solution, heating it to 70-85°C and maintaining it for 5-6 hours, cooling the mixture to room temperature, filtering it and drying it, and irradiating the dried product with microwaves under an argon atmosphere for 5 min-10 min to obtain a purified graphite product.

2. The method for purifying natural graphite in sections according to claim 1, wherein: The mass ratio of natural graphite to sodium hydroxide in step S1 is (2-4):

1.

3. The method for purifying natural graphite in stages according to claim 1, wherein: The grinding time in step S1 is 15-30 min.

4. The method for purifying natural graphite in stages according to claim 1, wherein: In step S3, the weight ratio of the product obtained in S2 to the hydrofluoric acid solution is 1:2-3.

5. The method for purifying natural graphite in stages according to claim 1, wherein: The concentration of the metal salt solution prepared in step S4 is 0.05-0.08 mol / L, and the mass ratio of the metal salt solution to the product obtained in S3 is 10-15:

1.

6. The method for purifying natural graphite in stages according to claim 5, characterized in that: The metal salt is one of nickel sulfate, iron nitrate, cobalt nitrate or chromium nitrate.

7. The method for purifying natural graphite in stages according to claim 1, wherein: The argon flow rate in step S4 is 1-2 L / min.

8. The method for purifying natural graphite in stages according to claim 1, characterized in that: The microwave frequency in steps S2 and S4 is 2450 MHz.

Citation Information

Patent Citations

  • Method for purifying graphite by using microwave

    CN102583360A

  • A process for preparing high-purity microcrystalline graphite with low energy consumption and in a large scale, and the high-purity microcrystalline graphite

    CN107555426A

  • Alkali-acid purification method of natural spherical graphite

    CN115974070A